PENGARUH KESELAMATAN KERJA, KESEHATAN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BIMA ARJUNA PRAKASA PADANG - Roni Ade Putra; Lidya Martha (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This study aims to test work safety on work productivity, to test occupational health on work productivity, to test the work environment on work productivity, this research was conducted at PT. Bima Arjuna Prakasa Padang. Sampling method using a total sampling saturation of 56 samples. The data analysis technique used is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, and t test. The results of the study indicate that work safety has a positive and significant effect on work productivity. Occupational Health has a positive and significant effect on work productivity, and the work environment has a positive and significant effect on work productivity. So it can be concluded that work safety is accepted, occupational health is accepted and the work environment is accepted